SUCCESION MANAGEMENT IN ROMANIAN SMEs - Vladislav ROTARU; Laurențiu Mihai; Radu OGARCĂ (Management & Marketing)
In this article, we intended to conduct an explorative analysis of how Romanian entrepreneurs relate to the issue of succession in their business. The data was collected through an online questionnaire, which was answered by 70 entrepreneurs. The main aspects investigated were the way in which Romanian entrepreneurs plan their retirement and succession and the preparation of future successors. Following this study, our main conclusion is that the owners of family businesses in Romania don’t yet see this issue as being important.